Isotope effects on particle transport in the Compact Helical System. (30th March 2016) - Tanaka, K; Okamura, S; Minami, T; Ida, K; Mikkelsen, D R; Osakabe, M; Yoshimura, Y; Isobe, M; Morita, S; Matsuoka, K
Abstract: The hydrogen isotope effects of particle transport were studied in the hydrogen and deuterium dominant plasmas of the Compact Helical System (CHS). Longer decay time of electron density after the turning-off of the gas puffing was observed in the deuterium dominant plasma suggesting that the recycling was higher and/or the particle confinement was better in the deuterium dominant plasma. Density modulation experiments showed the quantitative difference of the particle transport coefficients. Density was scanned from 0.8  ×  10 19 m −3 to 4  ×  10 19 m −3 under the same magnetic field and almost the same heating power. In the low density regime (line averaged density  <  2.5  ×  10 19 m −3 ), the lower particle diffusivity and the larger inwardly directed core convection velocity was observed in the deuterium dominant plasma, while in the high density regime (line averaged density  >2.5  ×  10 19 m −3 ) no clear difference was observed. This result indicates that the isotope effects of particle transport exist only in the low density regime. Comparison with neoclassical transport coefficients showed that the difference of particle transport is likely to be due to the difference of turbulence driven anomalous transport. Linear character of the ion scale turbulence was studied. The smaller linear growth rate qualitatively agreed with the reduced particle transport in the deuterium dominant plasma of the low density regime.